Botulinum Toxin in Migraine Treatment - Aydinlar, Elif Ilgaz; Dikmen, Pinar Yalinay; Kocaman, Ayse Sagduyu (TURKISH NEUROPSYCHIATRY ASSOC-TURK NOROPSIKIYATRI DERNEGI, 2013)
Since botulinum toxin might have a therapeutic effect on pain, many studies investigating the efficiency of botulinum toxin in headache treatment have been done. The most satisfying results were achieved by botulinum toxin type A (BoNT/A) in the treatment of chronic migraine. In this paper, we reviewed the clinical effectiveness of BoNT/A in migraine and included our clinical experience. In our ongoing pilot study, where we have repeated BoNT/A injections every 12 weeks, The difference in the Migraine Disability Assessment (MIDAS) scores between the first and the second injections was 61.1\%

and between the first and the 3rd injections was found to be 65.72\%.
Keywords: Botulinum toxin; chronic migraine; headache